Mechanical properties of concrete with clam shell powder as partal cement replacement - Majorie, Telun Avit (Universiti Malaysia Sarawak (UNIMAS), 2017)
Concrete is the backbone to the infrastructure development of a nation and the most important material that make a concrete workable is cement. The quality of cement reflects the character or strength of the concrete. However, the production consumes a lot of natural resources is not beneficial to the environment. There are researches conducted to find possible alternative materials to replace cement in concrete. Clam shell powder (CSP) is a type of municipal waste that is studied in this research. This research focuses on compressive strength of concrete containing different percentages of CSP. The amount of cement in concrete tested is replaced by 5%, 10% and 15% of CSP. The result of the compressive strength test is then compared to the conventional concrete, also known as control concrete. This control concrete does not contain any CSP. The result obtained show that CSP can be used as partial cement replacement material in concrete. The result obtained shows that the compressive strength increases as the percentage of CSP in concrete increases until the percentage reaches 15%. Concrete containing 15% CSP has lower compressive strength compared to concrete containing 5% and 10% CSP but still higher than the control concrete. It is also found out that the concrete containing 15% CSP is the most similar to the control concrete compared to the other specimens.